Why Is there a Limit to the Changes in Myofilament Ca2+-Sensitivity Associated with Myopathy Causing Mutations? - Marston, Steven B. (Frontiers in Physiology, 2016)
Mutations in striated muscle contractile proteins have been found to be the cause of a number of inherited muscle diseases; in most cases the mechanism proposed for causing the disease is derangement of the thin filament-based Ca2+- regulatory system of the muscle. When considering the results of experiments reported over the last 15 years , one feature has been frequently noted, but rarely discussed. The magnitude of changes in myofilament Ca2+-sensitivity due to myopathy- causing mutations in skeletal or heart muscle seems to be always in the range 1.5-3x EC50. Such consistency suggests it may be related to a fundamental property of muscle regulation; in this article we will investigate whether this observation is true and consider why this should be so. A literature search found 71 independent measurements of HCM mutation-induced change of EC50 ranging from 1.15 to 3.8-fold with a mean of 1.87±0.07 (sem) . We also found 11 independent measurements of increased Ca2+-sensitivity due to mutations in skeletal muscle proteins ranging from 1.19 to 2.7 fold with a mean of 2.00±0.16 Investigation of dilated cardiomyopathy-related mutations found 42 independent determinations show a range of EC50 wt/mutant from 0.3 to 2.3. In addition we found 14 measurements of Ca2+-sensitivity changes due skeletal muscle myopathy mutations ranging from 0.39 to 0.63. Thus our extensive literature search, although not necessarily complete, found that, indeed, the changes in myofilament Ca2+-sensitivity due to disease-causing mutations have a bimodal distribution and that the overall changes in Ca2+-sensitivity are quite small and do not extend beyond a 3 fold increase or decrease in Ca2+-sensitivity. We discuss two mechanism that are not necessarily mutually exclusive. Firstly, it could be that the limit is set by the capabilities of the Excitation-contraction machinery that supplies activating Ca2+ and that striated muscle cannot work in a way compatible with life outside these limits; or it may be due to a fundamental property of the troponin system and the permitted conformational transitions compatible with efficient regulation.